Indirect density tests for thin asphalt overlay – part 2: precision. Issue 1 (20th February 2019) - Xu, Yi; Nicklin, Samuel; Bull, Jack; Widyatmoko, Iswandaru
Abstract : This paper presents findings from a large-scale trial of thin asphalt overlay, with specific interest on assessing the precision of in situ density measurements under different moisture conditions and layer thickness. Three test methods were selected: the direct core density method (destructive) and two indirect (non-destructive) density methods. Indirect density measurements were found to be sensitive to pre-testing calibration and moisture condition. Statistical analysis was performed to establish the confidence intervals, variation and precision of the test results. A review of the literature, case studies and field testing suggested that the current equipment available on the market is not adequate for quality assurance (QA) purposes but acceptable for quality control. To improve the precision of indirect density gauges there should be a sound method for calibration, allowance for moisture and should only be considered for QA if ±5% variation from core densities can be demonstrated.